2021
DOI: 10.1002/jca.21899
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic plasma exchange and dextran‐sulfate plasma adsorption as extracorporeal treatments of extremely preterm preeclampsia with fetal growth restriction

Abstract: Aim To evaluate effectiveness and safety of therapeutic plasma exchange (TPE) and dextran‐sulfate plasma adsorption (DSA) for extracorporeal removal of soluble Fms‐like tyrosine kinase‐1 (sFlt‐1) as part of expectant management of preeclampsia at extremely preterm gestational age. Methods Retrospective case series of six patients with preeclampsia at <28 weeks of gestation, treated with DSA or TPE. Laboratory results, clinical characteristics and neonatal outcomes were collected from charts and National Perina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…Аферез є інвазивним методом, тому проводити великі клінічні випробування буде складно. Навіть без таких випробувань цей метод, ймовірно, може знайти місце у лікуванні захворювань, що виникають у ранньому терміні вагітності, де можливості обмежені, а прогноз примарний (аналогією може бути абдомінальний серкляж, запропонований жінкам, які мали повторні передчасні пологи на дуже ранніх термінах гестації, незважаючи на те що докази, які підтверджують цю техніку, є лише з серії випадків) [24].…”
Section: л е к ц і ї т а о г л я д иunclassified
“…Аферез є інвазивним методом, тому проводити великі клінічні випробування буде складно. Навіть без таких випробувань цей метод, ймовірно, може знайти місце у лікуванні захворювань, що виникають у ранньому терміні вагітності, де можливості обмежені, а прогноз примарний (аналогією може бути абдомінальний серкляж, запропонований жінкам, які мали повторні передчасні пологи на дуже ранніх термінах гестації, незважаючи на те що докази, які підтверджують цю техніку, є лише з серії випадків) [24].…”
Section: л е к ц і ї т а о г л я д иunclassified
“…8 In a recently published study, Gubensek et al showed that maternal stabilization can be achieved with dextran sulfate plasma adsorption (DSA) and therapeutic plasma exchange (TPE). 9 However, the researchers observed anaphylactic reactions and coagulation alterations, especially in patients treated with DSA, illustrating the need for an alternative sFlt-1 removal approach.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Thadhani et al were able to reduce the blood concentrations of sFlt‐1 in five women, yielding promising results with a reduction of preeclamptic symptoms and prolonging those pregnancies by at least 14 days 8 . In a recently published study, Gubensek et al showed that maternal stabilization can be achieved with dextran sulfate plasma adsorption (DSA) and therapeutic plasma exchange (TPE) 9 . However, the researchers observed anaphylactic reactions and coagulation alterations, especially in patients treated with DSA, illustrating the need for an alternative sFlt‐1 removal approach.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some progress has been made in the prevention and treatment of DSAs, mainly including physical adsorption and biological therapies . In vitro, the plasma exchange and immunoadsorption can reduce the serum DSA titer of patients to a certain extent; however, they are prone to supersaturation . Also, the risks of bleeding, allergy, and infection are still unavoidable, and they are still not applicable to patients with blood coagulation dysfunction. , Additionally, although the intervention strategies in vivo with gamma globulin and rituximab have achieved some efficacy, there are limitations such as low clearance efficiency, poor specificity, and bleeding. , In particular, a single-profile adsorption strategy is difficult to solve progressive and diverse subtype switching .…”
Section: Introductionmentioning
confidence: 99%
“…9 In vitro, the plasma exchange and immunoadsorption can reduce the serum DSA titer of patients to a certain extent; however, they are prone to supersaturation. 10 Also, the risks of bleeding, allergy, and infection are still unavoidable, and they are still not applicable to patients with blood coagulation dysfunction. 11,12 Additionally, although the intervention strategies in vivo with gamma globulin and rituximab have achieved some efficacy, there are limitations such as low clearance efficiency, poor specificity, and bleeding.…”
Section: Introductionmentioning
confidence: 99%